Teachers’ Competency on the Four Pillars of Digital Literacy in Guiding Students to Use Social Media Wisely - Paramansyah, Arman; Gunawan, Agus; Karmawan, Karmawan; Napitupulu, Hotma (Edusia: Jurnal Ilmiah Pendidikan Asia, 2023)
Technological development is rapid and unavoidable. Every individual, not limited to age, educational background, profession and others, can access information digitally. But unfortunately the rapid development of digital technology is not accompanied by the anticipation for its users. This is a qualitative research with a phenomenological approach. Data collection is done by Unstructure interview. The researchers classified the informants based on their teaching experience, namely (a) teachers with less than 10 years of teaching experience, (b) teachers with 10-20 years of teaching experience, and (c) teachers with more than 20 years of teaching experience. The results of the study show that not all teachers understand and implement digital literacy. Teachers with the old paradigm or those who on average have more than 20 years of teaching experience, do not give their students enough freedom in the aspects of digital skills, namely, critical thinking, creativity, communication skills and collaboration. Teachers with the old paradigm seem less able to accept criticism from their students or if there are things where students don't share the same ideas as their teachers. Teachers with the old paradigm also still have big concerns if their students collaborate with students from other schools for security reasons, and tend to direct students to use their electronic devices only for learning and not for other things. From the differences in perceptions among these teachers, education or training related to digital literacy for teachers is very urgent to be implemented.